1992
DOI: 10.1073/pnas.89.6.2017
|View full text |Cite
|
Sign up to set email alerts
|

Early hydrogen-bonding events in the folding reaction of ubiquitin.

Abstract: The formation of hydrogen-bonded structure in the folding reaction of ubiquitin, a small cytoplasmic protein with an extended (3-sheet and an a-helix surrounding a pronounced hydrophobic core, has been investigated by hydrogendeuterium exchange labeling in conjunction with rapid mixing methods and two-dimensional NMR analysis. The time course of protection from exchange has been measured for 26 backbone amide protons that form stable hydrogen bonds upon refolding and exchange slowly under native conditions. Am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
183
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(201 citation statements)
references
References 27 publications
18
183
0
Order By: Relevance
“…This is as fast as the folding of monomeric proteins where initial stages of folding occur on a time scale of less than about 5 ms and the final folding step to a well-structured state is rate limiting and occurs on a slower time. For example, native structure is formed in a few hundred ms in barstar (Nolting et al, 1997) and hen lysozyme (Radford et al, 1992), and in less than 20 ms in chymotrypsin inhibitor-2 (Jackson & Fersht, 1991) and less than 10 ms in ubiquitin (Briggs & Roder, 1992). With ppep-4, however, the folding process includes both dimer-dimer inter-molecular association and conformational re-shuffling to acheive the final folded state.…”
Section: Discussionmentioning
confidence: 99%
“…This is as fast as the folding of monomeric proteins where initial stages of folding occur on a time scale of less than about 5 ms and the final folding step to a well-structured state is rate limiting and occurs on a slower time. For example, native structure is formed in a few hundred ms in barstar (Nolting et al, 1997) and hen lysozyme (Radford et al, 1992), and in less than 20 ms in chymotrypsin inhibitor-2 (Jackson & Fersht, 1991) and less than 10 ms in ubiquitin (Briggs & Roder, 1992). With ppep-4, however, the folding process includes both dimer-dimer inter-molecular association and conformational re-shuffling to acheive the final folded state.…”
Section: Discussionmentioning
confidence: 99%
“…In the partially folded state of hen egg white lysozyme in trifluoroethanol (Buck et al, 1993), only little protection from deuterium/hydrogen exchanges could be observed for the amides located in a long loop while a majority of the observed protection occurred in helical regions. Experiments on the refolding reaction of ubiquitin (Briggs and Roder, 1992) indicated that while the amide protons from the beta sheet and the alpha helix as well as the protons involved in hydrogen bonding at the helixkheet interface become 80% protected in an initial 8-ms folding phase, somewhat slower protection rates were observed for the residues from a surface loop. In the partially folded species of lactalbumin, native secondary structures are largely formed while the loop regions remain disordered (Feng et al, 1994;Redfield et al, 1994).…”
Section: Kinetic Data On Protein Foldingmentioning
confidence: 99%
“…However, recent refolding experiments from denatured polypeptides of ribonuclease A (Udgaonkar and Baldwin, 1990), ribonuclease TI (Mul- lins et al, 1993). ubiquitin (Briggs and Roder, 1992), lysozyme , and staphylococcal nuclease (Jacobs and Fox, 1994) suggested that beta sheets can be formed at a rate comparable to that of alpha helices, and sometimes the residues in beta sheet are protected from hydrogeddeuterium exchange even before protection is observed in helices (Jacobs and Fox, 1994). However, the nuclease structures depend on several disulfide bridges and the helical domain of lysozyme as well as lactalbumin (Chyan et al, 1993) folds first.…”
Section: Kinetic Data On Protein Foldingmentioning
confidence: 99%
“…Ub populates a partially structured state (the socalled A-state) in the presence of alcohol in acidic solution at low salt (30), and this state was postulated to exist under a variety of other conditions (31), including those that favor correlated exchange regimes, where a distinction between this conformer and the native protein can be made based on markedly different levels of deuterium incorporation in HDX MS measurements (32). The A-state of Ub, the structure of which has been extensively characterized using NMR (33)(34)(35)(36)(37)(38) and other spectroscopic techniques (39), largely maintains the native secondary structure within the N-terminal part, whereas significant conformational changes within the C-terminal part eliminate the native fold and transform it into a transient helix. Top-down HDX MS characterization of the nonnative conformer of Ub reported in this work generates backbone-amide protection patterns fully consistent with the A-state of the protein and demonstrates that that top-down HDX MS/MS is capable of selective characterization of structural features of nonnative protein states without interference from other conformers coexisting in solution at equilibrium.…”
Section: Significancementioning
confidence: 99%